Long-term mental health outcomes after unintentional burns sustained during childhood: a retrospective cohort study. Issue 1 (13th November 2018) - Duke, Janine M.; Randall, Sean M.; Vetrichevvel, Thirthar P.; McGarry, Sarah; Boyd, James H.; Rea, Suzanne; Wood, Fiona M.
Abstract: Background: Burns are a devastating injury that can cause physical and psychological issues. Limited data exist on long-term mental health (MH) after unintentional burns sustained during childhood. This study assessed long-term MH admissions after paediatric burns. Methods: This retrospective cohort study included all children (< 18 years) hospitalised for a first burn ( n  = 11, 967) in Western Australia, 1980–2012, and a frequency matched uninjured comparison cohort ( n  = 46, 548). Linked hospital, MH and death data were examined. Multivariable negative binomial regression modelling was used to generate incidence rate ratios (IRR) and 95% confidence intervals (CI). Results: The burn cohort had a significantly higher adjusted rate of post-burn MH admissions compared to the uninjured cohort (IRR, 95% CI: 2.55, 2.07–3.15). Post-burn MH admission rates were twice as high for those younger than 5 years at index burn (IRR, 95% CI 2.06, 1.54–2.74), three times higher for those 5–9 years and 15–18 years (IRR, 95% CI: 3.21, 1.92–5.37 and 3.37, 2.13–5.33, respectively) and almost five times higher for those aged 10–14 (IRR, 95% CI: 4.90, 3.10–7.76), when compared with respective ages of uninjured children. The burn cohort had higher admission rates for mood and anxiety disorders (IRR, 95% CI: 2.79, 2.20–3.53), psychotic disorders (IRR, 95% CI: 2.82, 1.97–4.03) and mental and behavioural conditions relating to drug and alcohol abuse (IRR, 95% CI: 4.25, 3.39–5.32). Conclusions: Ongoing MH support is indicated for paediatric burn patients for a prolonged period after discharge to potentially prevent psychiatric morbidity and associated academic, social and psychological issues.